2007
DOI: 10.4081/ijas.2007.1s.698
|View full text |Cite
|
Sign up to set email alerts
|

Effects of slaughter weight and sex on carcass traits and meat quality of Casertana pigs reared outdoors

Abstract: The effects of different slaughter weights (W) and sex (S) on carcass traits and longissimus dorsi meat quality (pH, WHC, colour, cholesterol and collagen) of Casertana pigs were studied. Thirty-six pure breed Casertana pigs, 24 barrows (B) and 12 gilts (G), were evaluated in a 2x2 factorial design involving different slaughter live weights (L, 125.6 kg; H, 152.5 kg) and S (B and G). H pigs had higher carcass weight (P<0.01), dressing percentage (P<0.05), ham yield (+ 7.9 %; P<0.01), lean meat cuts (P<0.01) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
11
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 9 publications
8
11
1
Order By: Relevance
“…Conversely, Lan et al (1993) comparing muscle cholesterol content of several genetic types observed significant differences, but not among all breed studied. There are limited information in literature on the cholesterol content of the meat from CT pigs but the values detected in the present study for all the studied samples were quite high than that found by Maiorano et al (2007) and Salvatori et al (2008). The cholesterol content of pork reported in the literature varies.…”
Section: Meat Qualitycontrasting
confidence: 46%
See 4 more Smart Citations
“…Conversely, Lan et al (1993) comparing muscle cholesterol content of several genetic types observed significant differences, but not among all breed studied. There are limited information in literature on the cholesterol content of the meat from CT pigs but the values detected in the present study for all the studied samples were quite high than that found by Maiorano et al (2007) and Salvatori et al (2008). The cholesterol content of pork reported in the literature varies.…”
Section: Meat Qualitycontrasting
confidence: 46%
“…Other authors have reported a marked genetic effect on collagen properties in pigs (Lebret et al, 2001), beef (Campo et al, 2000) and lamb (Heinze et al, 1986). In addition, the literature documents growth rate-dependent Growth, carcass and meat quality of pigs shifts in muscle collagen amount and/or crosslinking (Aberle et al, 1981;McCormick, 1994;Harper, 1999;Maiorano et al, 2007). During rapid growth, newly synthesized collagen dilutes older collagen and is less crosslinked than the pre-existing collagen (Etherington, 1987), with a positive effect on meat tenderness (McCormick, 1994).…”
Section: Meat Qualitymentioning
confidence: 99%
See 3 more Smart Citations